Personalised campaigns in party-centred politics: Instagram and Facebook as arenas for political communication - Wan Mohd Ghazali, Wan Norshira; Mohamed, Shafizan; Abdul Manan, Kamaruzzaman (2019)
Social media like Facebook and Instagram place the focus on the individual politician rather than the political party, thereby expanding the political arena for increased personalised campaigning. The need to use social media to communicate a personal image as a politician and to post personalised messages online seems less obvious in a party-centred system of Malaysian politics. Within this framework, the personalised and dialogical aspects of social media may be contradicted with the political parties’ structural communication strategies. The study uses data from content analyses of eight Malaysian politicians’ Facebook and instagram accounts during the 14th General Election in Malaysia. The study adopts quantitative approach by presenting descriptive and exploratory analyses. The findings show that politicians’ depended more on facebook as their personal media platform and used instagram as an image booster. The study explains that different features offer by each platform serve as a determinant for politicians’ decision in using facebook and Instagram. The study concludes that both facebook and instagram push for personalization in political communication that requires private exposure and individual initiatives. Overall, the study shows that like other world leaders, Malaysian politicians are keeping abreast with the technology in reaching out various segments of the society for political communication.